Варіантність в офіційному жіночому іменослові України: між нормою й аномалією - Макарець, Ю. (Культура слова, 2020)
Стаття присвячена соціолінгвістичному аналізу сучасного
офіційного жіночого іменослову України. За даними Міністерства
юстиції України, репертуар імен новонароджених дівчат у
2015–2019 рр. становив майже тисячу одиниць. Інтенсивне
його розширення пов’язане з впливом глобалізаційних процесів на
іменування, відновленням національних традицій, зростанням
соціальної свободи у виборі імен, а часом і зі зниженням мовної
культури мовців. Майже третина одиниць, які Мін’юст фіксує як
окремі імена, є фонетико-орфографічними або морфологічними
варіантами. Варіантні ряди офіційного імені можуть сягати п’яти-
шести одиниць, що пов’язано з інтерференційними процесами,
наслідуванням іншомовної (здебільшого російської) вимови та
ігноруванням фонетичних і морфологічних рис української мови.
Такі варіанти не лише мають юридичні наслідки, але й негативно
впливають на мову: офіційний іменослов є атрибутом публічного
спілкування, і якщо варіант «повного» імені фіксує інтерференційне
явище, воно переходить із розмовної сфери в офіційну не як помилка,
а як санкціонований мовний факт. The article deals with sociolinguistic analysis of modern official
female onomasticon of Ukraine. Its dynamics reflects processes, which
are taking place in language system, and changes in society, social
demographic and ethnic pattern, cultural markers and values, even the
extent of legal regulation of social relations. Sociologists are interested
in personal names as a means of social categorization and differentiation
of individuals. Legists see them as a tool for one’s legalization and as an
object of legal protection. Anthropologists study them as special units of
communication and interaction between generations. For linguists they are
a specific typexplore them linguists – ists of means of lexical nomination.
Linguistically onomasticon is a valuable source of information on the
current state of language norms, level of linguistic culture of the population,
and the status correlation between languages in society.
According to the date of the Ministry of Justice of Ukraine, the repertoire
of newborn girls’ names in 2015–2019 exceeded half a thousand units. It’s
due to the magnitude of globalization processes in naming, restoration of
national naming traditions, rising social freedom in choosing names, and,
sometimes, the decay of sense of responsibility in naming and insufficient
language culture. About third part of female names appears as phonetic,
orthographic and morphological variants.
Ukraine is a multinational state and representatives of other nationalities
and national minorities maintain their own naming traditions. Ukrainian
spelling of these names in documents often is inconsequent. Often variants
arise due to the ambiguity of transliteration, Ukrainian-Russian language
interference and violation of Ukrainian spelling standard. Much less it is a
result of alive alternation in the Ukrainian language.
Rows of variants of the same official female name consist from two to
five or six units. Among them there are normative and anomalous variants.
In first case main and optional variants can be distinguished. Optional
variants are not conventional in language practice but they do not violate
the essential features of national language system (over time, some of
them may become more popular than the main variant). Linguistically
such variants are the same unit, the natural manifestation of potentialities
of language system. But legally, person’s name can’t be spelled differently
in her documents.